Extrusion of the Distal Catheter From the Umbilicus: A Case Report of a Rare Complication After Ventriculoperitoneal Shunt and Its Management - Yi Xia; Fang He; Zhen Ren; Chao Wang (Frontiers Media S.A., 2020)
Spontaneous extrusion of the distal catheter from the umbilicus following a ventriculoperitoneal shunt (VPS) for the treatment of hydrocephalus is an extremely rare complication. Here, we describe an 8-years-old boy who underwent a VPS for communicating hydrocephalus and thereafter the distal part of the catheter was extruded through the umbilicus. The extrusive part of the peritoneal catheter was successfully cut off with a laparoscope, keeping the remaining catheter in place and functional. The subsequent recovery process was uneventful. To the best of our knowledge, there have been no reports of using laparoscopy to cut the protruding part and replace the shunt end. By keeping the function of the original shunt pipe, this case report offers an innovative and informative approach to treating this complication.